Report of the joint select committee on the suspension of specie payments by the banks (Document (North Carolina. General Assembly), 1841)
January 6, 1841 report of the Joint Select Committee on the suspension of specie payments by the banks in the state. Of note, the Panic of 1837 resulted in a recession; and as noted in the report, northern banks began to suspend specie payments, meaning that they would no longer redeem commercial paper in specie at full face value. This report reviewed and investigated the situation regarding the State Bank and the Bank of Cape Fear. An appendix of various financial statements and correspondence was attached to the report.